Clinical characteristics, diagnosis, and risk stratification of pulmonary hypertension in severe tricuspid regurgitation and implications for transcatheter tricuspid valve repair. (16th March 2020) - Lurz, Philipp; Orban, Mathias; Besler, Christian; Braun, Daniel; Schlotter, Florian; Noack, Thilo; Desch, Steffen; Karam, Nicole; Kresoja, Karl-Patrik; Hagl, Christian; Borger, Michael; Nabauer, Michael; et al.
Abstract: Aims: Patients with pulmonary hypertension (PHT) are often excluded from surgical therapies for tricuspid regurgitation (TR). Transcatheter tricuspid valve repair (TTVR) with the MitraClip™ technique is a novel treatment option for these patients. We aimed to assess the role of PHT in severe TR and its implications for TTVR. Methods and results: A total of 243 patients underwent TTVR at two centres. One hundred twenty-one patients were grouped as iPHT+ [invasive systolic pulmonary artery pressures (PAPs) ≥50 mmHg]. Patients were similarly stratified according to echocardiographic PAPs (ePHT). The occurrence of the combined clinical endpoint (death, heart failure hospitalization, and reintervention) was investigated during a follow-up of 330 (interquartile range 175–402) days. iPHT+ patients were at higher preoperative risk ( P  < 0.01), had more severe symptoms ( P  = 0.01), higher N-terminal pro-B-type natriuretic peptide levels ( P  < 0.01), more impaired right ventricular (RV) function ( P  < 0.01), and afterload corrected RV function ( P  < 0.01). Procedural TTVR success was similar in iPHT+ and iPHT− patients (84 vs. 84%, P  = 0.99). The echocardiographic diagnostic accuracy to detect iPHT was only 55%. During follow-up, 35% of patients reached the combined clinical endpoint. The discordant diagnosis of iPHT+/ePHT− carried the highest risk for the combined clinical endpoint [HR 3.76 (CI 2.25–6.37), P  < 0.01], while iPHT+/ePHT+ patients had a similar survival-free time from the combined endpoint compared to iPHT− patients ( P  = 0.48). In patients with isolated tricuspid procedure ( n  = 131) a discordant iPHT+/ePHT− diagnosis and an impaired afterload corrected RV function ( P  < 0.01 for both) were independent predictors for the occurrence of the combined endpoint. Conclusion: The discordant echocardiographic and invasive diagnosis of PHT in severe TR predicts outcomes after TTVR.